On the cardinality of layers in even-valued n-dimensional lattice - T.V. Andreeva; Yu.S. Semenov (Учёные записки Казанского университета: Серия Физико-математические науки)
In this article, we explicitly calculated terms additional to the main one of cardinality asymptotics of central layers in the n-dimensional k-valued lattice Ekn for even k as n → ∞. The main term had been found by V.B. Alekseev for a certain class of posets. The case of odd k , which is technically less complicated, was the major focus of our previous work.